Alteration in glucocorticoids secretion and metabolism in patients affected by cystic fibrosis - Podgórski, Rafał; Sumińska, Marta; Rachel, Marta; Fichna, Marta; Fichna, Piotr; Mazur, Artur (Frontiers in Endocrinology, 2022)
Cystic fibrosis (CF) is an inherited syndrome associated with a mutation in a cystic fibrosis transmembrane conductance regulator gene, composed of exocrine gland dysfunction involving multiple systems that may result in chronic respiratory infections, pancreatic enzyme deficiency, and developmental disorders. Our study describes for the first time the urinary profile of glucocorticoid metabolites and the activity of the enzymes involved in the development and metabolism of cortisol in patients with CF, using a gas chromatography/mass spectrometry method. Data were obtained from 25 affected patients and 70 sex- and age- matched healthy volunteers. We have shown a general decrease in the activity of enzymes involved in the peripheral metabolism of cortisol, such as 11β-hydroxysteroid dehydrogenase type 2, 5α- and 5β-reductases. In contrast, the activity of 11β-hydroxysteroid dehydrogenase type 1, the enzyme that converts cortisone to cortisol, increased. Furthermore, our study found a significant decrease in glucocorticoid excretion in patients with CF. This may suggest adrenal insufficiency or dysregulation of the HPA axis and the development of peripheral mechanisms to counteract cortisol degradation in the case of reduced synthesis of glucocorticoids by the adrenal glands. Furthermore, the activity of 5α-reductase seems to be enhanced only through the backdoor pathway, especially when we taking into consideration 11β-hydroxyandrosterone/11β-hydroxyetiocholanolone ratio which has been shown to be the best differential marker for enzyme activity. CF impairs nutritional effects and energetic balance in patients; thus, our findings suggest the existence of adaptive mechanisms due to limited secretion of adrenal steroids and subsequent diminished amounts of their metabolites in urine. On the other hand, local control of cortisol availability is maintained by enhanced 11βHSD1 activity and its recovery from cortisone in organs and tissues which need this. Steroid hormone dysregulation might be another important factor in the course of CF that should be taken into account when planning an effective and comprehensive therapy.